Sustainable catalytic protocols for the solvent free epoxidation and anti-dihydroxylation of the alkene bonds of biorenewable terpene feedstocks using H2O2 as oxidant. Issue 2 (20th December 2019) - Cunningham, William B.; Tibbetts, Joshua D.; Hutchby, Marc; Maltby, Katarzyna A.; Davidson, Matthew G.; Hintermair, Ulrich; Plucinski, Pawel; Bull, Steven D.
Abstract : Solvent free catalytic epoxidation of biorenewable terpene feedstocks, including untreated crude sulfate turpentine. Abstract : A tungsten-based polyoxometalate catalyst employing aqueous H2 O2 as a benign oxidant has been used for the solvent free catalytic epoxidation of the trisubstituted alkene bonds of a wide range of biorenewable terpene substrates. This epoxidation protocol has been scaled up to produce limonene oxide, 3-carene oxide and α-pinene oxide on a multigram scale, with the catalyst being recycled three times to produce 3-carene oxide. Epoxidation of the less reactive disubstituted alkene bonds of terpene substrates could be achieved by carrying out catalytic epoxidation reactions at 50 °C. Methods have been developed that enable direct epoxidation of untreated crude sulfate turpentine to afford 3-carene oxide, α-pinene oxide and β-pinene oxide. Treatment of crude epoxide products (no work-up) with a heterogeneous acid catalyst (Amberlyst-15) results in clean epoxide hydrolysis to afford their corresponding terpene- anti -diols in good yields.